THE CONTRIBUTION OF ANXIETY TO ENGLISH TEXT COMPREHENSION ABILITY - Supeno Supeno; imam suseno (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2020)
This study aims to understand how anxiety as a variable contributes to affecting the ability to comprehend English texts using the ex post facto method, with eleventh grade high school students in Jakarta as the respondents. Students’ anxiety is measured based on behavioral and cognitive characteristics listed on the questionnaire given to respondents along with the English test. The results show that there is indeed a difference in anxiety levels on students in working on the various English text comprehension tests given. The results of the English text comprehension tests are generally influenced by the anxiety variable, although the effect is found to be small. Teachers are recommended to use multiple teaching methods, and to teach and motivate the students to read more. Teachers are also recommended to apply multiple variations of ability evaluation in measuring the students’ English text comprehension by using multiple test modes.